The five Senses between Illusion and Deception: sensory manipulations in some operas from Orlando furioso and Gerusalemme liberata (Itinera, 2017)
In Orlando Furioso and Jerusalem Delivered, Ariosto and Tasso granted a leading place to the sensory experience of their heroes. The manipulations of the senses allowed to deceive and charm them with seductive delusions by means of the beauty of their bodies and the wealth of their clothes, but also the delights of the feasts using the joy sometimes visual with the change of setting or auditive with the recurring presence of the music used as a background for these festivities. Moreover, we mustn’t forget another field of the knightly period which gives an importance to the five senses: that is the contentious dimension. Through the observation of seven operas booklets taken from the Orlando Furioso and Jerusalem Delivered  we will attempt to see how the singing theatre show this idea of sensory theatre in all its flamboyance.